Prediction of functional recovery six months following traumatic spinal cord injury during acute care hospitalization. (4th May 2018) - Denis, Andréane Richard-; Feldman, Debbie; Thompson, Cynthia; Mac-Thiong, Jean-Marc
Abstract : Objectives: To determine factors associated with functional status six months following a traumatic cervical and thoracic spinal cord injury (SCI), with a particular interest in factors related to the acute care hospitalization stay. Design: This is a prospective cohort study. Sixteen potential predictive variables were studied. Univariate regression analyses were first performed to determine the strength of association of each variable independently with the total Spinal Cord Independence Measure (SCIM) score. Significant ones were then included in a General linear model in order to determine the most relevant predictive factors among them. Analyses were carried out separately for tetraplegia and paraplegia. Setting: A single specialized Level I trauma center. Participants: One hundred fifty-nine patients hospitalized for an acute traumatic SCI between January 2010 and February 2015. Interventions: Not applicable. Main outcome measure: The SCIM (version 3) functional score. Results: Motor-complete SCI (AIS-A, B) was the main predictive factor associated with decreased total SCIM score in tetraplegia and paraplegia. Longer acute care length of stay and the occurrence of acute medical complications (either pneumonia, urinary tract infections or pressure ulcers) were predictors of decreased functional outcome following tetraplegia, while increased body mass index and higher trauma severity were predictive of decreased functional outcome following paraplegia. Conclusions: This study supports previous work while adding information regarding the importance of optimizing acute care hospitalization as it may influence chronic functional status following traumatic SCI.